(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to examine the role of administrative governance—represented by transparency, accountability, control, and commitment—in combating corruption within public institutions. The study adopted a descriptive analytical approach and employed a questionnaire as the main data collection tool. The study sample consisted of (45) employees specialized in the field of research, and the data were analyzed using appropriate statistical methods. The findings revealed a positive and statistically significant relationship between the level of administrative governance practices and the effectiveness of corruption prevention. The results also showed that transparency, accountability, and control have a stronger impact on reducing corruption compared to organizational commitment. Furthermore, the study confirmed that strengthening governance mechanisms enhances institutional performance, promotes integrity, and increases trust in public institutions. The study recommended reinforcing control systems, activating transparency principles, and developing legislative and regulatory frameworks to support anti-corruption efforts.